2022
DOI: 10.4103/jfmpc.jfmpc_1752_21
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana use experiences and expectancies of urban youth in India

Abstract: Objective: To gain information on the marijuana experiences and expectancies of youth in an urban Indian area, which may be used for forming the framework for the development of effective primary prevention strategies in the future. Method: This was a cross-sectional study conducted in various colleges of Mumbai; 260 students from three colleges who were above 18 years were selected by systematic random sampling. The participant had to fill a sociodemographic questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 24 publications
(23 reference statements)
1
10
0
Order By: Relevance
“…2,16 Prior studies among college students from India also had noted positive expectancies as well as ambivalent attitudes from use. 8,9,20 There can be several reasons for favorable attitudes or positive expectancies from cannabis use. For example, prior studies found that the students believed/used cannabis for relaxation, stress relief, enhancing creative abilities, better socialization, and increasing sexual desire.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2,16 Prior studies among college students from India also had noted positive expectancies as well as ambivalent attitudes from use. 8,9,20 There can be several reasons for favorable attitudes or positive expectancies from cannabis use. For example, prior studies found that the students believed/used cannabis for relaxation, stress relief, enhancing creative abilities, better socialization, and increasing sexual desire.…”
Section: Discussionmentioning
confidence: 99%
“…The MEEQ-B has been used in prior Indian studies. 9,19 The items in the Knowledge and Attitude tools were included based on a literature review, the research team's experience with college students, and consultations with experts in psychoactive substance use disorders. Furthermore, the items were guided by thematic content analysis of focus group discussions conducted with the college students, which explored their perceptions about cannabis use patterns, their beliefs about use, medical use, and legalization, and the potential impact of cannabis use on academics, relationships, and health.…”
Section: Original Articlementioning
confidence: 99%
See 2 more Smart Citations
“…They are assumed to provide the specialized cognitive processing needed for the highest neurocognitive performance. On a prolonged attentional processing test, marijuana usage before age 16 was linked to a shorter reaction time [ 29 ]. Cannabis use alters the endocannabinoid system, impacting executive function, reward function, and affective functions.…”
Section: Reviewmentioning
confidence: 99%